Preliminary Study of PGA Fabric for Seromas at Latissimus Dorsi Flap Donor Sites. Issue 10 (October 2017) - Itani, Yoshihito; Hagiwara, Akeo; Hashimoto, Takahiro; Isogai, Noritaka; Kusuhara, Hirohisa
Abstract : Background: Seroma formation is a major complication following latissimus dorsi (LD) flap transfer for breast reconstruction. We implanted a nonwoven polyglycolic acid (PGA) fabric—a biodegradable polymer—in the LD flap donor site and examined its effect on postoperative seroma formation and resolution in a comparative study on 38 patients undergoing primary 1-stage breast reconstruction by LD flap. Method: A PGA treatment group had a PGA fabric placed in the donor wound (PGA group, n = 20), whereas a second group was treated with standard donor site closure (control group, n = 18). The incidence of seromas was comparable between the groups. Result: There was a significant reduction in aspiration volume by needle aspiration after drain removal ( P < 0.05) and in the time until seroma resolution ( P < 0.01) in the PGA group compared with the control group. Conclusion: These results indicate that application of PGA at the LD donor site is useful in controlling postoperative seromas.